Vitamin C Promotes Astrocyte Differentiation Through DNA Hydroxymethylation. (31st July 2018) - Kim, Jong-Hwan; Kim, Mirang; He, Xi-Biao; Wulansari, Noviana; Yoon, Byoung-Ha; Bae, Dong-Hyuck; Huh, Nanhyung; Kim, Yong Sung; Lee, Sang-Hun; Kim, Seon-Young
Abstract : Previous studies have reported that vitamin C (VC) promotes neural stem/precursor cell (NSC) differentiation toward dopamine (DA) neurons via DNA hydroxymethylation-induced transcriptional activation of DA neuron-specific genes. To further understand the VC effects on NSC differentiation, we profiled the transcriptome and DNA methylome/hydroxymethylome using high-throughput sequencing. Interestingly, RNA sequencing analyses have shown that, in addition to DA neuronal genes, astrocytic genes Gfap, Slc1a3, and S100a16 were also upregulated in NSC cultures differentiated with VC treatment. Consistently, enhanced GFAP+ astrocytic yields were manifested in the differentiated cultures with VC treatment, collectively indicating that VC promotes astrocytic differentiation. In genome-wide hydroxymethylome analyses, VC treatment induces enrichment of DNA hydroxymethylation (5-hydroxymethyl cytosine; 5hmC) near the consensus binding motifs of nuclear factor I (NFI). Furthermore, we showed that VC significantly enhanced recruitment of NFI and STAT3, key transcription factors for astrogenesis, in the 5hmC-enriched regions of the astrocyte-specific genes. These findings suggest that VC play important roles in astrocytogenesis during brain development. Abstract : Treatment of neural stem cells with VC modulates the DNA hydroxymethylation of astrocytic genes such as Gfap, which increases gene expression. And also DNA hydroxymethylation increases at the binding site of astrocyte associated transcription factors near the astrocytic genes. By these epigenomic changes, VC treatment of neural stem cells stimulates differentiation into astrocyte.